2011
DOI: 10.1097/id.0b013e3182263665
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Histopathologic Evaluation of Bioactive Glass and Human-Derived Graft Materials in Macaca fascicularis Mandibular Ridge Reconstruction

Abstract: Numerous particles of nonresorbed bioactive glass graft material, but not human demineralized bone matrix, were found in 4-year posttreatment bone core biopsies of regenerated bone in M. fascicularis mandibular alveolar ridge reconstructions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
(8 reference statements)
0
5
0
Order By: Relevance
“…Bioactive glass is an osteoconductive biomaterial that has been used as a bone substitute for periodontal defects, alveolar filling, and in apical resections [31][32][33][34][35][36] . However, few prospective clinical studies have demonstrated the behaviour of this material in maxillary sinus augmentation with a sufficiently large number of patients 37,38 .…”
Section: Discussionmentioning
confidence: 99%
“…Bioactive glass is an osteoconductive biomaterial that has been used as a bone substitute for periodontal defects, alveolar filling, and in apical resections [31][32][33][34][35][36] . However, few prospective clinical studies have demonstrated the behaviour of this material in maxillary sinus augmentation with a sufficiently large number of patients 37,38 .…”
Section: Discussionmentioning
confidence: 99%
“…Each bone defect was closed and sutured by a skin‐matrix barrier membrane‐covered flap in front of the mucoperiosteal tissue. At 4 years posttreatment, alveolar bone at all sites was clinically normal, and mature cortical and cancellous bone formation was observed histologically in both bone graft materials 104 . Boller et al 105 created defects (15 mm × 8 mm × 5 mm) on both sides of the mandibles of nine baboons.…”
Section: Implantation Defect Models (Include Alveolar Ridge Expansion...mentioning
confidence: 99%
“…Suzuki et al 104 created bilateral bone defects in the edentulous mandibular alveolar ridge of nonhuman primates, which were grafted with two different types of bone graft materials. Each bone defect was closed and sutured by a skin‐matrix barrier membrane‐covered flap in front of the mucoperiosteal tissue.…”
Section: Implantation Defect Models (Include Alveolar Ridge Expansion...mentioning
confidence: 99%
See 1 more Smart Citation
“…The use of bioactive glasses as alloplastic bone graft materials for alveolar ridge augmentation [68][69][70][71] and maxillary sinus lift [72][73][74] procedures has received increasing attention in implant dentistry. Besides Bioglass® other commercial types of bioactive glass have been used for bone repair such as PerioGlas® [70,75,76] and BioGran® [71][72][73]. Studies have reported presence of bioactive glass long-term postoperative (1-2 years) [72,73].…”
Section: Formulamentioning
confidence: 99%